Petrologia e geocronologia do stock granodiorítico Lagoa do Roçado, domínio Mucururé, faixa sergipana-SE - Silva, Cleverton Correia (2014)
The Lagoa do Roçado Granodioritic Stock is a body with approximately 12 km2, elongated intrusive in metasediments Macururé Domain, located in central region of Sergipana Belt. The rocks that make up this stock are gray color, predominantly equigranular, occurring sometimes inequigranular. In the central part of the body occurs frequently, the presence of microgranular mafic enclaves. Petrographic studies allowed to identify that this stock is essentially composed of granodiorite with biotite, hornblende and diopside, with the accessories, titanite, allanite, pistacita, zircon, apatite and opaque minerals. Geochemical data show that its rocks are calc-alkaline high potassium microgranular mafic enclaves with showing affinity with the shoshonitic suite. The good linear correlation identified in Harker diagrams between felsic and mafic types is suggestive that the process of magma mixing is responsible for the chemical variation found . The spectra of the rocks have REE fractionation of light REE relative to heavy REE and a weak negative anomaly in Eu, indicating fractionation of plagioclase. These rocks thrown when the tectonic affinity diagrams of Pearce (1996), positioned in the post-tectonic granites field. Isotopic analyzes for zircon sample of biotite-hornblende-granodiorite (187A), were obtained by SHRIMP IIe at Geochronology Laboratory of the Universidade de São Paulo . The zircon crystals are exhibited as elongated prisms with length versus width proportions 3:1. Cathodoluminescence images reveal that these crystals show up clear or oscillatory zoning, typical of magmatic zircon. Data U/Pb zircon ages reveal a concordant age of 618 ± 4 Ma (MSWD = 0.7). This is similar to the age old crystallization obtained by Long et al. 2005 for Coronel João Sá Massif (626 ± 2 Ma) located in the western part of the Macururé Domain, which presents petrographic and geochemical characteristics similar to the Lagoa do Roçado Granodioritic Stock. The age obtained for these rocks suggests that the Lagoa do Roçado Granodioritic Stock is positioned as the late to posttectonic in relation to the Brasiliano Orogeny.